"Los Bienaventurados”: a Meeting with Fernando Soto Aparicio. A tribute in his 82-year birthday (2016)
At the end of our literary journey through this text, sharing the company of the Reading Club from Universidad Militar Nueva Granada, we will learn through literatore, specifically from the literary work of the Colombian writer Fernando Soto Aparicio and his novel “Los Bienaventurados”, how reality emerges itself, and how those “fictional” worlds glide by our past, present and future, to awaken us in Colombia today, to make us finally ask about the issue of peace post-conflict.